2018
DOI: 10.1109/tdei.2018.007158
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved gas analysis of thermal faults in transformer liquids simulated using immersed heating method

Abstract: Dissolved gas analysis (DGA) is considered as one of the most effective techniques to diagnose transformer incipient faults. With the increasing applications of alternative liquids in transformers, fault gas generation characteristics of the liquids were investigated in laboratory under simulated faults. Immersed heating method has been widely used to simulate thermal faults, of which the complete fault temperature range was hardly achieved. In this paper, pool boiling theory was introduced to explain the unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 13 publications
2
22
0
Order By: Relevance
“…-The heating element should achieve a temperature in the range from 150 • C to 450 • C and keep it for about two hours. The authors of the papers [10], [22], [23] reported that in this temperature range the generation of gases was observed, while the two-hour time allowed to generate measurable gas concentrations.…”
Section: Measurement Setups 1) Preparation Of the Heating Elementmentioning
confidence: 97%
See 4 more Smart Citations
“…-The heating element should achieve a temperature in the range from 150 • C to 450 • C and keep it for about two hours. The authors of the papers [10], [22], [23] reported that in this temperature range the generation of gases was observed, while the two-hour time allowed to generate measurable gas concentrations.…”
Section: Measurement Setups 1) Preparation Of the Heating Elementmentioning
confidence: 97%
“…3) Heating the liquid flowing through the heated pipeclosed liquid circuit: the container with cold oil → furnace → the container with cold oil [20], [21]. 4) Local heating of the insulating liquid using a heating element immersed in it [10], [22], [23]. According to the authors, the local overheating of the insulating liquid by means of heating element immersed in it best suits the conditions of such a defect in the real transformer.…”
Section: State Of the Artmentioning
confidence: 99%
See 3 more Smart Citations